Impact of mentoring on organisational role stress and role efficacy: an empirical evidence from India. (2nd August 2022) - Shauran, Bharti; Jain, Neetu
This study examines the impact of career and psychosocial mentoring on the role efficacy and organisational role stress of employees. Survey methodology was used to test the hypotheses. The sample was randomly selected amongst the employees working in the IT sector in Delhi and National Capital Region (NCR), India. A total of 220 complete responses were received where 89 employees did not have any mentor and 131 employees were mentored. A pilot study was carried out to develop valid data items for the survey and to test the reliability and internal consistency. The findings indicate that mentoring plays a significant role in improving role efficacy and in reducing organisational role stress in the case of mentored employees as compared to non-mentored employees.